2017
DOI: 10.2196/resprot.7419
|View full text |Cite
|
Sign up to set email alerts
|

Simple Wound Irrigation in the Postoperative Treatment for Surgically Drained Spontaneous Soft Tissue Abscesses: Study Protocol for a Prospective, Single-Blinded, Randomized Controlled Trial

Abstract: BackgroundSkin abscesses are a frequent encountered health care problem and lead to a significant source of morbidity. They consequently have an essential impact on the quality of life and work. To date, the type of aftercare for surgically drained abscesses remains under debate. This leads to undesirable practice variations. Many clinical standard protocols include sterile wound dressings twice a day by a home-care service to reduce the chance of a recurrent wound infection. It is unknown, however, whether re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The quality of this prospective trial with comparable infection rates between the NSI and SI groups warrants the recommendation to use tap water irrigation for wound healing by secondary intention. With 6.8%, we are well in the range of trials comparing NSI and SI for open wound treatment [9, 23], even though clearly lower than our power analysis assumed [14]. A potential explanation for this might be the relatively low rate of MRSA in our study, with only 5.9% compared to trials presenting incidence rates of approximately 60% [24].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The quality of this prospective trial with comparable infection rates between the NSI and SI groups warrants the recommendation to use tap water irrigation for wound healing by secondary intention. With 6.8%, we are well in the range of trials comparing NSI and SI for open wound treatment [9, 23], even though clearly lower than our power analysis assumed [14]. A potential explanation for this might be the relatively low rate of MRSA in our study, with only 5.9% compared to trials presenting incidence rates of approximately 60% [24].…”
Section: Discussionmentioning
confidence: 59%
“…The study was approved by the medical ethics research committee and registered with the Ethikkomission Nordwest und Zentralschweiz (EKNZ) [BASEC 2016-00002] and the German Clinical Trials Register [DRKS00010418]. The study protocol has been published previously [14]. The trial was in accordance with the ''Ethical standards of the Helsinki Declaration of 1975''.…”
Section: Methodsmentioning
confidence: 99%
“…15 Furthermore, Rühle et al reported on multiple options for irrigation fluid and nonsterile wound irrigation. 16 Different antiseptic irrigation materials all have their varied advantages and disadvantages. However, sterile saline is the least problematic fluid with which to wash the wound.…”
Section: Discussionmentioning
confidence: 99%
“…In the spring and summer of 2016, two prospective randomized clinical trials in a non-academic teaching hospital in Switzerland were initiated. The scientific substance of these two studies was unrelated to the current study and details are described elsewhere [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Trial one: Postoperative treatment of surgically drained spontaneous soft tissue abscesses [10] The goal of this trial is to prove the non-inferiority of more easily applicable postoperative wound care after surgically treated soft tissue abscesses, aiming to empower the patient with independent wound care and a shorter period of time off work.…”
Section: Trialsmentioning
confidence: 99%